2020
DOI: 10.1108/ijge-06-2019-0101
|View full text |Cite
|
Sign up to set email alerts
|

Performance drivers of women-owned microcredit funded enterprises in Tanzania

Abstract: Purpose The purpose of this paper is to investigate performance drivers of women-owned businesses that are funded primarily through microcredit. It draws on Storey’s theory of small business growth and family embeddedness axiom to examine the factors that drive the performance of businesses that are funded primarily through microcredit. Design/methodology/approach The paper uses a cross-sectional survey that covered 208 women business owners who had access to microcredit. The authors use a logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 59 publications
(85 reference statements)
0
8
0
Order By: Relevance
“…The finding also shows that an increase in one unit of amount of loan borrowed was associated with a higher odds of being in the higher income group with and odds ratio of 2.044 (e 0.715 , p < 0.05). This finding is supported by Tundui and Tundui (2020) who also found that total amount of loans received from micro finance institution has significantly influenced the performance of the borrowers to generate more income.…”
Section: Ordinal Logistic Regressionmentioning
confidence: 65%
“…The finding also shows that an increase in one unit of amount of loan borrowed was associated with a higher odds of being in the higher income group with and odds ratio of 2.044 (e 0.715 , p < 0.05). This finding is supported by Tundui and Tundui (2020) who also found that total amount of loans received from micro finance institution has significantly influenced the performance of the borrowers to generate more income.…”
Section: Ordinal Logistic Regressionmentioning
confidence: 65%
“…Studies [21,22] undertaken in Tanzania on influence of group based micro-financial services found that the welfare of group based borrower households had improved more compared to those of non or individual based borrowers. That is, household assets, children education and medical treatments of group based borrowers' households were better than those of individual based and/ or non-borrower households [7,3].…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…Anecdotal evidence (e.g., case studies, videos, and success stories) highlight that at least some women fully or partially use microfinance for entrepreneurial purposes. Women use microfinance for business start-up and development purposes such as purchasing assets or stock, upgrading existing equipment, or paying for marketing (Mahmood, 2011;Tundui and Tundui, 2020). The opportunity for direct investment of loans in ventures also provide a platform for entrepreneurial learning (Sigalla and Carney, 2012).…”
Section: Microfinance and Its Effects On Womenmentioning
confidence: 99%